Barriers and enablers encountered by bereaved informal motor neuron disease (MND) caregivers when trying to access bereavement support: a qualitative cross-sectional thematic analysis of semistructured interviews with 6–36 months postbereavement informal MND caregivers in the UK - Laura Cramond; Liberty Braben; Deepsi Khatiwada; Belinda F Bradley; Suresh K. Chhetri (BMJ Open)
Background Caregivers of people with motor neuron disease (MND) face more negative consequences of caregiving than other terminal illnesses. The impact of this caregiver burden can negatively influence bereavement outcomes.Objectives This study aims to explore the support needs of caregivers of people with MND, the types of bereavement services they use, or the reasons for not using bereavement services, and understanding the opportunities and barriers to accessing bereavement services.Design The design of the study was a qualitative interview study using thematic analysis following the method of Braun and Clarke (2006).Setting and participants Twenty bereaved caregivers of people with MND were purposively sampled. Participants were recruited through the Lancashire and South Cumbria MND Care and Research Centre.Results Thematic analysis revealed four overarching themes: (1) type of support accessed, (2) the importance of people who understand, (3) barriers to accessing support, and (4) being (un)prepared for death and afterwards.Conclusions Caregivers of people with MND require people who understand their unique needs to support them, alongside professional support, to prepare them for the death of their loved one and beyond. Barriers to accessing support included the need for in-person support, insufficient financial support or signposting to relevant services and being unprepared for death and bereavement.